What is the role of the subventricular zone in radiotherapy of glioblastoma patients?. (May 2021) - Bender, Katja; Träger, Malte; Wahner, Helena; Onken, Julia; Scheel, Michael; Beck, Marcus; Ehret, Felix; Budach, Volker; Kaul, David
Highlights: Patients with glioblastoma lesions in contact with the subventricular zone show worse overall survival. Irradiation of the subventricular zone does not improve progression-free or overall survival. Confirmatory prospective trials are needed. Abstract: Background and purpose: Current glioblastoma (GBM) therapies prolong survival, but overall prognosis is still poor. Irradiation of the subventricular zone (SVZ) has recently been discussed as a promising concept as this tissue harbors stem cells which seem to play a role in the initiation and recurrence of GBM. In this study, we retrospectively examined the relationship of SVZ irradiation dose and survival in a large, homogeneous GBM patient cohort. Materials and methods: We included 200 GBM patients who had been treated at our institution with trimodal therapy (surgery, radiotherapy and chemotherapy) between 2009 and 2020. The SVZ was delineated, and dose-volume histograms were calculated and extracted. Tumors were classified according to their contact with the SVZ. The Kaplan-Meier method was used for survival analysis, and univariable and multivariable Cox regression (MVA) were used to determine prognostic effects on progression-free survival (PFS) and overall survival (OS). Results: Median PFS of the study group was 7.2 months; median OS was 15.1 months. In MVA (with mean dose to the ipsilateral SVZ as a continuous covariable), PFS was significantly lower for patients with a Karnofsky performance status (KPS) < 70% and without MGMT promoter methylation. Factors prognostic for shorter OS were old age, lower KPS, unmethylated MGMT status, SVZ contact and biopsy instead of subtotal- or gross total resection. There was no significant correlation between survival and SVZ dose. Conclusion: In this cohort, an increased mean dose to the ipsilateral or contralateral SVZ did not correlate with improved survival in irradiated GBM patients in MVA. Patients whose tumor directly involved the SVZ showed worse OS in MVA.